Hazardous materials chemistry for emergency responders - Burke, Robert (CRC Press, 2013)
"Written in the same clear, concise style that made the previous editions bestsellers, this book provides easy to understand chemistry for responders to use to handle hazardous materials emergencies on a daily basis. It provides the fundamentals of "street chemistry" that emergency response personnel need to know, with a focus on hazmat elements. This edition includes new review questions with answers and new incident examples. It also introduces the new United Nations GHS system for classification and labeling of chemicals, updates the NFPA requirements, and provides information on ethanol and other alternative automotive fuels"-- Provided by publisher.
Keywords: Hazardous substances.; elektronické knihy; electronic books